Exertional esophageal pH-metry and manometry in recurrent chest pain - Budzyński, Jacek (Baishideng Publishing Group Co., Limited, 2010)
AIM: To investigate the diagnostic efficacy of 24-h and exertional esophageal pH-metry and manometry in patients with recurrent chest pain. METHODS: The study included 111 patients (54% male) with recurrent angina-like chest pain, non-responsive to therapy with proton pump inhibitors. Sixty-five (59%) had non-obstructive lesions in coronary artery angiography, and in 46 (41%) significant coronary artery narrowing was found. In all patients, 24-h esophageal pH-metry and manometry, and treadmill stress tests with simultaneous esophageal pH-metry and manometry monitoring were performed. During a 24-h examination the percentage of spontaneous chest pain (sCP) episodes associated with acid reflux or dysmotility (symptom index, SI) was calculated. Patients with SI > 50% for acid gastroesophageal reflux (GER) were classified as having GER-related sCP. The remaining symptomatic individuals were determined as having non-GER-related sCP. During the stress test, the occurrence of chest pain, episodes of esophageal acidification (pH < 4 for 10 s) and esophageal spasm with more than 55% of simultaneous contractions (exercise-provoked esophageal spasm or EPES) were noted. RESULTS: Sixty-eight (61%) individuals reported sCP during 24-h esophageal function monitoring. Eleven of these (16%) were classified as having GER-related sCP and 53/68 (84%) as having non-GER-related sCP. The exercise-provoked chest pain during a stress test occurred in 13/111 (12%) subjects. In order to compare the clinical usefulness of 24-h esophageal function monitoring and its examination limited only to the treadmill stress test, the standard parameters of diagnostic test evaluation were determined. The occurrence of GER-related or non-GER-related sCP was assumed as a “gold standard”. Afterwards, accuracy, sensitivity and specificity were calculated. These parameters expressed a prediction of GER-related or non-GER-related sCP occurrence by the presence of chest pain, esophageal acidification and EPES. Accuracy, sensitivity and specificity of chest pain during the stress test predicting any sCP occurrence were 28%, 35% and 80%, respectively, predicting GER-related sCP were 42%, 0% and 83%, respectively, and predicting non-GER-related sCP were 57%, 36% and 83%, respectively. Similar values were obtained for exercise-related acidification with pH < 4 longer than 10 s in the prediction of GER-related sCP (44%, 36% and 92%, respectively) and EPES in relation to non-GER-related sCP (48%, 23% and 84%, respectively). CONCLUSION: The presence of chest pain, esophageal acidification and EPES had greater than 80% specificity to exclude the GER-related and non-GER-related causes of recurrent chest pain.